Characterization of composite materials based on PP-Cork blends - Ben Abdallah, F. (2006)
This article studies the possibility of making a cork fiber to reinforce plastics (polypropylene, PP). The thermal and structural properties of natural fibers are determined. The hydrophilic character of cork and the hydrophobic character of PP eliminate all chemical adhesion between the fiber and the matrix. This article gives a method of surface modification of cork which ameliorates the fiber–matrix adhesion (their results effects on the mechanical properties of composites). The method consists of hot water treatment. First, the influence of water treatment on the mechanical, thermal, and structural properties of the cork used to reinforce the composites is studied. This study is used to prepare a composite material with good mechanical and thermal properties without destruction of the cellular structure. The specimens of cork are treated with boiling water at ambient pressure for 1, 2 and 3 h and then washed with cold water. The specimens are dried in a dry oven at 70 C for 3 h. The results obtained show that density decreases as a function of water treatment time. This study also describes the influence of water treatment on the thermal behavior of the cork. An increase in thermal stability with water treatment time, in a nitrogen atmosphere, is noticed. In an isothermal study, a loss of mass of 5% after 30 min at 180 C is observed. The specimens of treated and untreated cork are used to reinforce the PP matrix. The tensile test shows the importance of the surface modification of cork used in composites, particularly after treatment for 1 h. The adhesion properties of PP–cork are described with scanning electron microscopy (SEM).